2021
DOI: 10.1021/acs.jmedchem.1c01021
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I) Bis(1,2,3-triazol-5-ylidene) Complexes as Promising Selective Anticancer Compounds

Abstract: The synthesis and antiproliferative activity of Mes-and iPr-substituted gold(I) bis(1,2,3-triazol-5-ylidene) complexes in various cancer cell lines are reported, showing nanomolar IC 50 values of 50 nM (lymphoma cells) and 500 nM (leukemia cells), respectively (Mes < iPr). The compounds exclusively induce apoptosis (50 nM to 5 μM) instead of necrosis in common malignant blood cells (leukemia cells) and do not affect non-malignant leucocytes. Remarkably, the complexes not only overcome resistances against the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 61 publications
(110 reference statements)
0
15
0
Order By: Relevance
“…Notably, it does not affect non-malignant white blood cells and can overcome the drug resistance. 66 Iacopetta reported two NHC–Au–NHC complexes and explored their mechanism of action. The results showed that 34 and 35 are inhibitors of the actin polymerization reaction with similar efficacy to cytochalasin B but do not influence F-actin depolymerization.…”
Section: Gold(i) Complexes As Anticancer Agentsmentioning
confidence: 99%
“…Notably, it does not affect non-malignant white blood cells and can overcome the drug resistance. 66 Iacopetta reported two NHC–Au–NHC complexes and explored their mechanism of action. The results showed that 34 and 35 are inhibitors of the actin polymerization reaction with similar efficacy to cytochalasin B but do not influence F-actin depolymerization.…”
Section: Gold(i) Complexes As Anticancer Agentsmentioning
confidence: 99%
“…The activation of HRK by HB324 that is shown by Western blot analysis ( Figure 3 c) should be further verified by a cell model. The daunorubicin-resistant subcellline (NiWi-Dau) of chronic myeloid leukemia cells K562 has been shown in previous studies to under-express HRK [ 9 ]. The experiment showed that the complex cannot cause any effect on the cells ( Figure 3 d) with this mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, research has focused on substances that selectively induce apoptosis in malignant cells and at low concentrations. We and others have reported on novel metal-based compounds that can overcome these resistances and have a low toxicity [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Metal complexes have long been of big interest in modern cancer research [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past several decades, because copper (Cu) is an essential metal in the human body and plays a vital role in biological functions, Cu compounds have been extensively studied as the promising next-generation anticancer metal drugs. Interestingly, many studies have shown that metal compounds can kill cancer cells through multiple mechanisms, overcome the resistance of cancer cells to cisplatin, and inhibit their metastasis. Currently, it has been one of the most effectively strategies for the treatment of cancer through acting on the different components of the tumor micro-environment (TME). , Therefore, we may overcome the resistance of NSCLC cells to cisplatin and inhibit their metastasis by rationally designing a new Cu agent that acts on the different components in the TME.…”
Section: Introductionmentioning
confidence: 99%